Energy Efficient Cooperative Communications in Aggregated VLC/RF Networks with NOMA - Rallis, Konstantinos G.; Papanikolaou, Vasileios; Diamantoulakis, Panagiotis D.; Tegos, Sotiris A.; Dowhuszko, Alexis A.; Khalighi, Mohammad Ali; Karagiannidis, George K. (IEEE Transactions on Communications, 2023)
Optimizing the energy efficiency (EE) of wireless networks is one of the key priorities in the design of beyond 5G mobile technologies. In this pursuit, the use of new frequency bands, in combination with advanced multiple access protocols and cooperative communications strategies, has recently shown promising results. To this end, this paper investigates an indoor wireless network that aggregates communication resources in visible light and radio-frequency (RF) bands, taking advantage of the complementary aspects of the two technologies. More specifically, a non-orthogonal multiple access (NOMA) scheme is introduced for the visible light communication (VLC) downlink, such that cell-edge users experiencing a weak VLC signal enhance their aggregated data rate with the aid of cooperative communications over RF sidelinks (i.e., device-to-device links). The optimal resource allocation strategy over both VLC and RF bands is derived aiming at EE maximization based on the Dinkelbach’s algorithm and successive convex approximation. Additionally, for the sake of flexibility, a weighted EE metric is proposed for the characterization of the aggregated VLC/RF network performance. Simulation results are provided to validate the proposed analysis, revealing the impact of various design and system parameters, such as the weighting factors, quality of service requirements, and channel conditions.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Aggregated VLC/RF networks; Cooperative NOMA; Energy efficiency; Energy efficiency; Hybrid power systems; NOMA; Protocols; Radio frequency; Resource allocation; Resource management; Sidelink communications; Visible light communication; Visible light communications